2013
DOI: 10.1111/tri.12198
|View full text |Cite
|
Sign up to set email alerts
|

A formula to calculate the standard liver volume in children and its application in pediatric liver transplantation

Abstract: SummaryDue to a lack of available size-matched liver grafts from children, most pediatric recipients are transplanted with technical variant grafts from adult donors. Size requirements for these grafts are not well defined, and consequences of mismatched graft sizes in pediatric liver transplantation are not known. Existing formulas for calculation of a standard liver volume are mostly derived from adults disregarding the age-related percentual liver weight changes in children. In this study, we aimed to estab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 19 publications
3
23
1
3
Order By: Relevance
“…Six children in group 3 received large‐size grafts (GRWR >4%), these large grafts could fit well into the abdomen, and the recipients achieved equal outcome with other recipients who received size‐matched organs. Thus, our data supported the previous report that large‐for‐size transplantation in children did not influence the postoperative outcomes …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Six children in group 3 received large‐size grafts (GRWR >4%), these large grafts could fit well into the abdomen, and the recipients achieved equal outcome with other recipients who received size‐matched organs. Thus, our data supported the previous report that large‐for‐size transplantation in children did not influence the postoperative outcomes …”
Section: Discussionsupporting
confidence: 92%
“…Thus, our data supported the previous report that large-for-size transplantation in children did not influence the postoperative outcomes. 32 In spite of the fact that neonatal (group 1) and infant (group 2) grafts seemed to have higher rate of SFSS, the recipients in these two groups showed favorable outcome in acute rejection, and the recipients in group 3 exhibited significantly higher rate of acute rejection compared with the combination of groups 1 and 2 in our study. It has long been claimed that immune tolerance is more likely to be induced in children due to the immatureness of immune system.…”
Section: Discussioncontrasting
confidence: 65%
“…When considering the standard liver volume using the formula proposed by Herden et al [13], we found an estimated standard liver volume ranging from 460.75 cc to 1089.76 cc, with a median of 876.37 cc, a mean ± sd of 820.81 ± 245.69 cc. The percentage of future liver remnant (FLR) of total liver volume (TLV) ranged from 14.7% to 39.3%, with a median of 25.5%, a mean ± sd of 25.5 ± 8%.…”
Section: Resultsmentioning
confidence: 99%
“… 0 to ≤1 year of age: SLV (mL) = −143.062973 + 4.274603051 × height (cm) + 14.78817631 × weight (kg) >1 to <16 years of age: SLV (mL) = −20.2472281 + 3.339056437 × height (cm) + 13.11312561 × weight (kg) >16 years of age: SLV (mL) = 1072.8 × ([weight (kg)] 0.425 × [height (cm)] 0.725 × 0.007184) − 345.7 …”
Section: Methodsmentioning
confidence: 99%